Rhetoric and Renaissance culture - Plett, Heinrich F. (De Gruyter, 2004)
Since Jacob Burckhardt's Kultur der Renaissance in Italien (1869) rhetoric as a significant cultural factor of the renaissance has largely been neglected. The present study seeks to remedy this deficit regarding the arts by concentrating on literary theor.